Design a mixer for grain materials - Mohd Hisyam Ismail (Universiti Malaysia Perlis, 2008)
Polymers are materials composed of molecules of high molecular weight. These large molecules are generally called macromolecules. Because of their low density and their ability to be shaped and molded at relatively low temperatures compared to traditional materials such as metals, plastics and polymers are the materials of choice when integrating several parts into a single component. Polymers processing now become more advances in this world. Nowadays, a lot of machine to process polymers such as extrusion, injection molding, blow molding, thermoforming and also film blowing. Extrusion is one of the processes used to process polymers to produce plastic materials such as flat films and sheets, pipes and tubular films for bags, filaments and strands, hollow profiles for window frames and open profiles. At this time, for the extrusion process, polymers materials that are used have mixed with other materials before put it in the hopper. This project more concentrated on how to absorb 4 kinds of material and transfer it into hopper automatically following the sequences. To make it easy way, new automatic control systems had to propose to produce more fast and effective. Programmable Logic Control (PLC) is one of programmable controller that used to control this system. Objectives of this project are to create an automatic system to replace manual system especially that is used in small and medium industries.